A Comparison of Energy Profile between Castilla Leon, Spain and Aceh, Indonesia - Mahidin Mahidin; Khairil Khairil; Carmen Martin; Miguel A. Villamanan; Jose J. Segovia; Cesar R. Chamorro (Jurnal Rekayasa Kimia & Lingkungan, 2010)
A comparative study on energy production and consumption between Aceh, Indonesia and Castilla León, Spain has been conducted. Analysis was carried out on the statistical data such as population, GDP, energy production and energy consumption. Some interesting results were obtained. An average energy production during 2001 – 2004 in Aceh is up to 28 times of the average energy production in Castilla León; however, the average energy consumption during those four years is only 16.74% of the average energy consumption of Castilla León. Aceh's average GDP from 2001 to 2004 is 3,357.16 million Euros, stands at only 8.15% of Castilla León's average GDP about 41,175.75 million Euros.